Pematahan Dormansi Benih Selada menggunakan Konsentrasi Benzyladenine dan Penyinaran yang Berbeda: Lettuce Seed Dormancy Breaking using Different Radiation and Benzyladenine Concentration - Fariroh, Indri; Tri Handoyo; Riza Yuli Rusdiana (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2024)
Secondary dormancy in lettuce seeds which is triggered by high temperatures and darkness is caused low germination in nurseries. This issue must be solved to obtain high-quality seeds. The experimental design used factorial randomized complete block design, i.e., 6-benzyladenine concentration (0, 0.05, 0.1, 0.5, 1 mM) and radiation treatment (light, dark, red light 1, 2, 3 hours) with 3 replicates. The lettuce varieties used Grand Rapids (GR) and Ava Red (AR). The parameters observed were the percentage of seed germination (SG), seed vigor index (SVI), seed growth rate (SGR), and fresh seed that did not grow (FSdnG). Data were analyzed using ANOVA, the treatment which showed significant effect further tested using Duncan Multiple Range Test at α = 5%. The result showed that GR seed without BA soaking resulted in higher SG (39.20%), SVI (26.13%), SGR (12.04%), also lower FSdnG (6.13%). The highest percentage of SVI in GR seed was reported on light treatment (26.93%). Radiation of red light for 1 hour without seed soaking in BA produced higher SG (76%) and SGR (29.98%) in Ava Red. The highest percentage of SVI in Ava Red was obtained from seeds without soaking in BA (53.33%) and germinated in light conditions (34.93%).Keywords: BAP, photodormancy, red light, skotodormancy